2019
DOI: 10.1038/s41467-019-10706-y
|View full text |Cite
|
Sign up to set email alerts
|

Urinary tract colonization is enhanced by a plasmid that regulates uropathogenic Acinetobacter baumannii chromosomal genes

Abstract: Multidrug resistant (MDR) Acinetobacter baumannii poses a growing threat to global health. Research on Acinetobacter pathogenesis has primarily focused on pneumonia and bloodstream infections, even though one in five A. baumannii strains are isolated from urinary sites. In this study, we highlight the role of A. baumannii as a uropathogen. We develop the first A. baumannii catheter-associated urin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
139
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 105 publications
(147 citation statements)
references
References 77 publications
5
139
0
Order By: Relevance
“…Although research on A. baumannii infections has primarily focused on pneumonia and bloodstream infections, recent claims are that one in five A. baumannii strains are isolated from urinary sites [51]. A. baumannii occasionally causes urinary tract infections (UTIs), especially with indwelling urinary catheters [4], and was responsible for 1.6% of ICU-acquired UTIs in one study [52].…”
Section: Urinary Tract Infectionsmentioning
confidence: 99%
“…Although research on A. baumannii infections has primarily focused on pneumonia and bloodstream infections, recent claims are that one in five A. baumannii strains are isolated from urinary sites [51]. A. baumannii occasionally causes urinary tract infections (UTIs), especially with indwelling urinary catheters [4], and was responsible for 1.6% of ICU-acquired UTIs in one study [52].…”
Section: Urinary Tract Infectionsmentioning
confidence: 99%
“…One subset of strains secretes Hcp under standard laboratory conditions, indicating that they possess a constitutively active (or offensive) T6SS. A second subset of strains possess a silenced T6SS because they harbor a family of multidrug-resistance plasmids named large conjugative plasmids (LCPs), which transcriptionally repress the T6SS locus (40)(41)(42). The final subset of A. baumannii strains expresses T6SS-related genes and does not harbor an LCP but does not secrete Hcp under standard laboratory conditions (39,(43)(44)(45).…”
mentioning
confidence: 99%
“…Often, controlled drug delivery systems rely on sustained passive delivery, although this often results in exposure of bacterial pathogens to sub-lethal antimicrobial doses. Additionally, the release of antimicrobial compounds may also be hindered by the deposition of host proteins onto the catheter due to inflammatory response caused by the urinary catheterization [64,65,150,[166][167][168]. All of these together may explain why promising coating technologies in vitro yield mixed results when tested in clinical trials [102].…”
Section: Challenges In Fighting Cautismentioning
confidence: 99%
“…By understanding the host response to urinary catheterization and infection, more efficient coating and modifications can be developed. Recently, it was found that one of the host proteins released by the inflammatory response, fibrinogen, is essential for biofilm formation in vivo by several prevalent uropathogens such as enterococcal strains, methicillin-resistant S. aureus, Acinetobacter baumannii, and even the fungal pathogen C. albicans [64,65,150,[166][167][168]. The fact that different groups of pathogens use host proteins for biofilm formation suggests a common pathway for colonization in the catheterized environment.…”
Section: Challenges In Fighting Cautismentioning
confidence: 99%